Science advice and global environmental governance : expert institutions and the implementation of international environmental treaties - Kohler, Pia M. (Anthem international environmental policy series., 2020)
"Science Advice and Global Environmental Governance" examines expert committees established to provide advice on science to multilateral environmental agreements. By focusing on how these institutions are sites of coproduction of knowledge and policy, this work brings to light the politics of science advice and details how these committees are contributing to an emerging global environmental constitutionalism. Grounded in participant observation, elite interviews and document analysis, this book uses the lenses of the body of experts, body of knowledge and institutional body to focus on three treaties: the Montreal Protocol on Substances That Deplete the Ozone Layer, the Stockholm Convention on Persistent Organic Pollutants and the UN Convention to Combat Desertification.